Simulation of the performance of HVAC systems and central plant for energy calculations: a component based modelling approach - Obanor, A. I. (Cranfield University, 1985)
In recent years, operational prediction and optimisation of heating, ventilating and air conditioning (HVAC) systems and central plant to minimise the energy required to maintain building indoor conditions have become increasingly important. To effectively design and implement an energy management program for building energy systems, a simulation study must be performed. This thesis describes research conducted into the development of a modular simulation program for analysing the performance of HVAC systems and central plant. The computer program uses a quasi-steady state modelling approach and is able to simulate a wide variety of systems which are configured using available component models. Steady state mathematical models of HVAC components are developed using fundamental heat and mass transfer principles, laws of conservation of mass and energy and where appropriate empirical data. The carponent models are formulated to allow for the effects of various control strategies on the performance of systems and plant to be investigated. The program is applied to simulate a part of the Collins' Building variable air volume (VAV) air conditioning system and a hypothetical central cooling plant. The results of the simulation exercises are presented and analysed. The issue of validation and building energy simulation models is discussed. Conclusions are drawn and recommendations for further work are made.